Identifying the mentorship needs among faculty in a large department of psychiatry- support for the creation of a formal mentorship program - Mary Jane Esplen; Lisa M. Fiksenbaum; Elizabeth Lin; Shaheen A. Darani; John Teshima; Simone N. Vigod; Nicole Kozloff; Peter Szatmari; Krista L. Lanctôt; Certina Ho; Ivan Silver; Sophie Soklaridis; et al. (BMC Medical Education)
Abstract Background Study aims were to assess the current state and needs of faculty to inform the design of a formal mentorship program in a large academic Department of Psychiatry. Methods A 57- item self-administered online survey questionnaire was distributed to all faculty members. Results 225 faculty members completed the survey (24%). 68% of respondents had a mentor and reported high satisfaction (mean = 4.3, SD = 1.05) (range 1 to 5). Among those respondents lacking access to mentorship, 65% expressed interest. Open-ended questions indicated that international medical graduates, faculty identifying as minority, women and clinician teachers may lack access to mentorship. PhD faculty felt disadvantaged compared to MD faculty in gaining first authorship (M Non−MD=1.64 ± 0.79 vs. MMD=1.36 ± 0.67; t = 2.51, p = .013); reported more authorship disputes (M Non−MD =1.99 ± 0.91 vs. MMD =1.66 ± 0.76; t = 2.63 p = .009) and experienced questionable scientific integrity concerning colleagues (M Non−MD =2.01 ± 0.92 vs. MMD =1.70 ± 0.81; t = 2.42 p = .017). For both MD and PhD faculty, women were significantly more likely to experience authorship disputes (χ2(2) = 8.67, p = .013). The department was perceived as treating faculty with respect (72% agreed) with 54% agreeing that it embraces diversity (54%). Identified benefits to mentorship included receiving advice about academic promotion, opportunities for career advancement, advocacy, and advice as a researcher, teacher or clinician. Only 26% of mentors received formal training to support their role; 59% expressed interest in education. Respondents supported a more formal, accessible, inclusive program, with training, tools, and a matching strategy based on mentee preferences. Conclusions Challenges and inequities were identified with the department’s current ad hoc approach to mentorship. A limitation of the study was the response rate, while similar to response rates of other physician surveys, raises the potential for response bias. In comparing study participants to the department, the sample appeared to provide a fair representation. The study has implications for identifying the need and design of more formal mentorship programs in academic medicine.